2018
DOI: 10.1002/14651858.cd012504.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for investigating and identifying the causes of stillbirth

Abstract: There is currently a lack of RCT evidence regarding the effectiveness of interventions for investigating and identifying the causes of stillbirth. Seeking to determine the causes of stillbirth is an essential component of quality maternity care, but it remains unclear what impact these interventions have on the psychosocial outcomes of parents and families, the rates of diagnosis of the causes of stillbirth, and the care and management of subsequent pregnancies following stillbirth. Due to the absence of trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…As less than 1% of the pregnant women included in this analysis were enrolled and treated in the first trimester, the risk of congenital abnormality due to antimalarial drugs is expected to be very low in the current study. Congenital abnormalities in stillborns were presumably underreported, but autopsy or chromosomal investigation was not mentioned in any of the study sites [63,64]. Due to the availability of information, placental pigmentation was analysed only qualitatively, while a previous study revealed AL reduced the level of pigmentation more than quinine [53].…”
Section: Discussionmentioning
confidence: 99%
“…As less than 1% of the pregnant women included in this analysis were enrolled and treated in the first trimester, the risk of congenital abnormality due to antimalarial drugs is expected to be very low in the current study. Congenital abnormalities in stillborns were presumably underreported, but autopsy or chromosomal investigation was not mentioned in any of the study sites [63,64]. Due to the availability of information, placental pigmentation was analysed only qualitatively, while a previous study revealed AL reduced the level of pigmentation more than quinine [53].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple logistic regression was performed for variables with p < 0.1 in the univariate analysis. We also included variables that were risk indicators reported in previous studies (age, parity and ethnicity [ 7 , 12 , 17 , 18 ]). The results of the multiple logistic regression were reported as adjusted odds ratio (aOR).…”
Section: Methodsmentioning
confidence: 99%
“…Stillbirths should be systematically assessed to identify risk factors and causes and provide strategies for reducing the SBR [ 6 ]. Obtaining reliable statistics is challenging since stillbirths are often poorly documented by the vital registry [ 4 – 7 ]. A literature review [ 8 ] revealed that, between 2009 and 2014, more than 81 systems were in place to classify causes of perinatal deaths, complicating cross-country comparison [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 Decreasing the global burden of stillbirth mainly focuses on strategic interventions and to enable these strategic interventions to minimize stillbirth rate, identification of risk factors of stillbirth is needed. 9 The risk factors of a large proportion of stillbirths remain unknown despite an improvement in antenatal and intrapartum care and extensive testing. 10,11 Previous studies have identified that several factors were linked with the occurrence of stillbirth.…”
Section: Introductionmentioning
confidence: 99%